Globalisation, concentration and footloose firms: in search of the main cause of the declining labour share - John Hutchinson; Damiaan Persyn (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2009)
Over the last two decades the share of national income which accrues to labour has followed a marked downward trend across a host of industrialised countries. This paper attempts to assess the importance of several potential causes of this phenomenon. We investigate compositional effects, the effect of declining trade costs, changes in the market structure (concentration) and the effect of low-wage competition between countries. Overall, the findings suggest that lower trade costs and factors related to economic integration such as industry concentration, the market power of firms and increased international low-wage competition indeed affect the labour share. However, their effect has been quite limited when compared to changes in the sectoral composition, the effects of technological change, cyclical factors and changes in the prices of intfirmediary goods.
Keywords: J30; E25; 330; factor shares; globalisation; Wirtschaftsintegration; Internationaler Wettbewerb; Lohnquote; Transportkosten; Marktstruktur; Dekompositionsverfahren; EU-Staaten